CCP encyclopedia of Philippine art. (CCP, 1994)
The CCP encyclopedia is a 10-volume collection of reference materials on the Philippine arts and culture. The first two volumes are comprehensive information about the people of our country and the last volume provides general index arranged alphabetically by topics. Subject heading chronologically arranged from volume 3 are architecture, visual arts, dance, theater, literature, music and film.